(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2020)
Background: Food labeling is a tool to promote and protect public health by providing accurate nutritional information so that consumers can make informed dietary choices, while others consider it as an instrument of marketing and product promotion. Objective: A descriptive study was conducted to assess the Knowledge, Attitude and Practices (KAP) of the population regarding Food Labels. Methodology: Data was gathered using a KAP Questionnaire which included questions of socio demographic profile, knowledge, attitude and practice from hundred (100) adult subjects whether working/non working of Kalkaji area of South Delhi. Results: Descriptive statistics analyzed knowledge, attitudes, and behaviors of subjects regarding food labels. It was found out that subjects mean knowledge score was 58%. Knowledge score was positively correlated with attitude score towards food labels (r = 0.44, P ≤ 0.01) and similarly knowledge score was also positively correlated with practices of the same (r = 0.31, P ≤ 0.01). The results showed that only 45% of the subjects knew about food labels out of which 8% strongly agreed that food label is anything which is written on food package, 28% agreed that a logo or a picture on a food package is a food label, 41% agreed that nutritional information is a food label, 40% strongly agreed that expiry/ manufacturing date on a food package is a food label and majority of the subjects (93%) practice reading food labels. Conclusion: Nutrition labeling can be an effective means of helping consumers to make healthful food choices. Regulations can play a crucial role in enhancing the potential for nutrition labeling and health claims to promote health. The effectiveness of nutrition labeling and health claims in improving national dietary patterns relies largely on a motivated and educated public to make healthful choices.